The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1525-1314.2006.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic constraints on age and duration of fluid‐assisted high‐pressure eclogite‐facies recrystallization during exhumation of deeply subducted continental crust in the Sulu orogen

Abstract: Fluid availability during high-grade metamorphism is a critical factor in dictating petrological, geochemical and isotopic reequilibration between metamorphic minerals, with fluid-absent metamorphism commonly resulting in neither zircon growth/recrystallization for U-Pb dating nor Sm-Nd isotopic resetting for isochron dating. While peak ultra-high pressure (UHP) metamorphism is characterized by fluid immobility, high-pressure (HP) eclogite-facies recrystallization during exhumation is expected to take place in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 109 publications
(136 reference statements)
3
51
0
Order By: Relevance
“…This method follows the idea that the state of intermineral O isotope equilibrium may be a good indicator of with slope of unity that best fit the data for each locality represent the same degree of Mg isotope fractionation between clinopyroxene and garnet (i.e., the same Δ 26 Mg clinopyroxene-garnet value) at the same temperature. Error bars indicate the external precision of ±0.07 ‰ (2SD) on δ 26 Mg. Data are from Table 2 the state of Nd isotope equilibrium between clinopyroxene and garnet in eclogites (Zheng et al 2002(Zheng et al , 2003Zhao et al 2006). This is because the attainment of isotopic exchange equilibrium between mineral pairs and its preservation during later geological processes (e.g., retrograde metamorphism) is controlled by diffusion.…”
Section: Selection Of Equilibrium Mg Isotope Fractionation Between CLmentioning
confidence: 99%
“…This method follows the idea that the state of intermineral O isotope equilibrium may be a good indicator of with slope of unity that best fit the data for each locality represent the same degree of Mg isotope fractionation between clinopyroxene and garnet (i.e., the same Δ 26 Mg clinopyroxene-garnet value) at the same temperature. Error bars indicate the external precision of ±0.07 ‰ (2SD) on δ 26 Mg. Data are from Table 2 the state of Nd isotope equilibrium between clinopyroxene and garnet in eclogites (Zheng et al 2002(Zheng et al , 2003Zhao et al 2006). This is because the attainment of isotopic exchange equilibrium between mineral pairs and its preservation during later geological processes (e.g., retrograde metamorphism) is controlled by diffusion.…”
Section: Selection Of Equilibrium Mg Isotope Fractionation Between CLmentioning
confidence: 99%
“…Along the Dabie-Sulu belt, the UHP rocks were rapidly exhumed to crustal levels along the Dabie-Sulu orogenic belt (e.g., Zhao et al, 2006;Liu et al, 2008a;Zheng et al, 2009). In the meantime, the SCB finally collided with the NCB along the Qinling orogen (e.g., Jiang et al, 2010).…”
Section: A Possible Model For Mesozoic Geodynamics Of the Scbmentioning
confidence: 99%
“…Geochemical studies have demonstrated that supracrustal material was subducted to mantle depth of more than 120 km, recrystallized within a short time span under UHP metamorphic condition and then was rapidly exhumed (e.g., Zheng et al 2003c). The time period for the UHP/HP metamorphism has been constrained between 215 and 245 Ma by different radiometric methods (Li et al 1993(Li et al , 2000Ames et al 1996;Hacker et al 1998;Chavagnac et al 2001;Ayers et al 2002;Liu et al 2004a, b;Liu et al 2006a, b;Wu et al 2006;Zhao et al 2006). The Sulu UHP-HP belt is located between the Wulian-Qingdao-Yantai fault in the northwest and the Jiashan-Xiangshui fault in the south (Fig.…”
Section: Geological Settingmentioning
confidence: 98%
“…On the basis of radiometric dating and O isotope analysis on UHP metamorphic rocks in the DabieSulu orogenic belt, Zheng et al (2002) proposed that the O isotopic composition can be used as an indicator to test the conditions of Nd and Sr isotopic equilibrium of metamorphic minerals. Subsequently, abundant studies on eclogite, gneiss, and granite in the Dabie-Sulu orogenic belt have shown that d 18 O variation between cogenetic minerals can provide a reasonable test to the validity of mineral Sm-Nd and Rb-Sr chronometers (Zheng et al 2002(Zheng et al , 2003aLi et al 2004;Xie et al 2004Xie et al , 2006Zhao et al 2006). Most of these studies have shown that the Sm-Nd isotopic system preserves the information of UHP eclogite-facies metamorphism and Sm-Nd mineral isochrons of eclogite and gneiss give UHP metamorphic ages.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation